Muscular synergism during core stability exercises - Leporace, G.; Praxedes, J.; Metsavaht, L.; Pinto, S.; Chagas, D.; Pereira, G.; Batista, L. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The aim of this study was to compare the myoelectric activity and synergism of Core region muscles among exercises commonly prescribed for Core training. The myoelectric activity of seven men was collected and the activation ratio among lumbar erector spinae (LES), lumbar multifidus (MT), external oblique (EO) and rectus abdominis (RA) were compared among eight exercises. The results suggest that EO has higher activation during frontal bridge, side bridge and "bird dog" exercises, RA has higher activation during frontal and side bridge, while LES and MT demonstrated higher activation during "bird dog" and double leg and single leg back bridge. We concluded that to train all muscles groups in a synergic way, in different postures, it should be prescribed at least one variation of the exercises that presents the flexor, lateral flexor and extensor pattern.